The agenda of the national written press towards political issues - alber, wafa; djeffal, samia (Journal of Social Sciences and Humanities, 2024)
Written journalism as a medium of the media is a tool of political change and education. It is an important source of obtaining information on political issues that increases awareness and political knowledge about community issues research the concerns of Al-Khabar newspaper towards local political issues. In the period between 01 October to 30 December 2019, by studying what the location of these issues is in the newspaper, how frequently they occur and in what the audience is targeting, our study which indicate that the nature of the coverage on which Al-Khabar newspaper relies on political issues is the presentation of facts, information, statements and all developments related to the case.